(untitled) (Eurasian Research Bulletin, 2024)
This paper examines the profound impact of information technology (IT) on human life, examining its pervasive presence in various fields, including communication, education, health, commerce, and entertainment. It highlights the multifaceted importance of IT in connectivity, information dissemination, innovation and empowerment, thereby changing the fabric of modern society. Through a comprehensive examination of key areas, emerging trends, and ethical considerations, this paper seeks to highlight the critical role of information technology in enhancing human empowerment, promoting societal progress, and shaping the future trajectory of human existence in an increasingly interconnected world